Characterization and overproduction of cell-associated cholesterol oxidase ChoD from Streptomyces lavendulae YAKB-15 - Keith Yamada; Arina Koroleva; Mitchell Laughlin; Niko Oksanen; Amir Akhgari; Vera Safronova; Elena Yakovleva; Vera Kolodyaznaya; Tatiana Buldakova; Mikko Metsä-Ketelä (NATURE PUBLISHING GROUP, 2022)
Cholesterol oxidases are important enzymes with a wide range of applications from basic research to industry. In this study, we have discovered and described the first cell-associated cholesterol oxidase, ChoD, from Streptomyces lavendulaeYAKB-15. This strain is a naturally high producer of ChoD, but only produces ChoD in a complex medium containing whole yeast cells. For characterization of ChoD, we acquired a draft genome sequence of S. lavendulaeYAKB-15 and identified a gene product containing a flavin adenine dinucleotide binding motif, which could be responsible for the ChoD activity. The enzymatic activity was confirmed in vitro with histidine tagged ChoD produced in Escherichia coli TOP10, which lead to the determination of basic kinetic parameters with K-m 15.9 mu M and k(cat) 10.4/s. The optimum temperature and pH was 65 degrees C and 5, respectively. In order to increase the efficiency of production, we then expressed the cholesterol oxidase, choD, gene heterologously in Streptomyces lividans TK24 and Streptomyces albus J1074 using two different expression systems. In S. albus J1074, the ChoD activity was comparable to the wild type S. lavendulaeYAKB-15, but importantly allowed production of ChoD without the presence of yeast cells.